The Exnovation of Chronic Care Management Processes by Physician Organizations - RODRIGUEZ, HECTOR P. (Milbank Q, 2016)
POLICY POINTS: The rate of adoption of chronic care management processes (CMPs) by physician organizations has been fairly slow in spite of demonstrated effectiveness of CMPs in improving outcomes of chronic care. Exnovation (ie, removal of innovations) by physician organizations largely explains the slow population‐level increases in practice use of CMPs over time. Expanded health information technology functions may aid practices in retaining CMPs. Low provider reimbursement by Medicaid programs, however, may contribute to disinvestment in CMPs by physician organizations. CONTEXT: Exnovation is the process of removal of innovations that are not effective in improving organizational performance, are too disruptive to routine operations, or do not fit well with the existing organizational strategy, incentives, structure, and/or culture. Exnovation may contribute to the low overall adoption of care management processes (CMPs) by US physician organizations over time. METHODS: Three national surveys of US physician organizations, which included common questions about organizational characteristics, use of CMPs, and health information technology (HIT) capabilities for practices of all sizes, and Truven Health Insurance Coverage Estimates were integrated to assess organizational and market influences on the exnovation of CMPs in a longitudinal cohort of 1,048 physician organizations. CMPs included 5 strategies for each of 4 chronic conditions (diabetes, asthma, congestive heart failure, and depression): registry use, nurse care management, patient reminders for preventive and care management services to prevent exacerbations of chronic illness, use of nonphysician clinicians to provide patient education, and quality of care feedback to physicians. FINDINGS: Over one‐third (34.1%) of physician organizations exnovated CMPs on net. Quality of care data feedback to physicians and patient reminders for recommended preventive and chronic care were discontinued by over one‐third of exnovators, while nurse care management and registries were largely retained. Greater proportions of baseline Medicaid practice revenue (incidence rate ratio [IRR] = 1.44, p < 0.001) and increasing proportions of revenue from Medicaid (IRR = 1.02, p < 0.05) were associated with greater CMP exnovation by physician organizations on net. Practices with greater expansion of HIT functionality exnovated fewer CMPs (IRR = 0.91, p < 0.001) compared to practices with less expansion of HIT functionality. CONCLUSIONS: Exnovation of CMPs is an important reason why the population‐level adoption of CMPs by physician organizations has remained low. Expanded HIT functions and changes to Medicaid reimbursement and incentives may aid the retention of CMPs by physician organizations.